Kil Tabletlerden Elektronik Yayıncılığa Kütüphanecilik Felsefesinin Gelişimi ve Dönüşümü - Mehmet Toplu (Türk Kütüphaneciliği)
Although, the librarianship as an institution traces its history back to 5000 years, it has acquired its identity as a scientific discipline in the second part of the 19th century, as many other branches of the science. The philosophical aspect of the librarianship has begun to be discussed since 1930's, after many years later than these developments. In librarianship, application aspect and professional quality had a stronger influence, but philosophical and theoretical discussions have been rather limited to academic community. Although, the subjects such as ethics, the liberty of thought and the liberty of statement are important in the discipline of librarianship, it has never been taken into account that these subjects have been also fundamental to the philosophy in general. In the earlier periods of the philosophy of librarianship the focus was on the institution of librarianship and information sources, however with the development of electronic publishing these perception has begun to change, and information and knowledge has been brought into sharp focus. In this work, it is studied how the librarianship has evolved in the historical process, how this evolution has affected the appearance of the philosophical and theoretical aspects of the librarianship, which philosophical views have been at the forefront in certain periods.